Конституційно-правова природа Ради Міністрів Автономної Республіки Крим: дискусійні питання теорії та практики - Чабан, А.А. (Часопис Київського університету права, 2010)
У статті розкриваються особливості конституційно-правової природи Ради міністрів Автономної Республіки Крим. Показане місце Ради міністрів Автономної Республіки Крим серед інших органів публічної влади. Ключові слова: Рада міністрів Автономної Республіки Крим, Автономна Республіка Крим, уряд, автономія. В статье раскрываются особенности конституционно-правовой природы Совета министров Автономной Республики Крым. Показано место Совета министров Автономной Республики Крым среди других органов публичной власти. Ключевые слова: Совет министров Автономной Республики Крым, Автономная Республика Крым, правительство, автономия. In the article the features of constitutional and legal status of the Rada of Ministry of the Autonomous Republic of Crimea are analyzed. The place of the Rada of Ministry of the Autonomous Republic of Crimea between others organs of public power is defined. Key words: the Rada of Ministry of the Autonomous Republic of Crimea, the Autonomous Republic of Crimea, government, autonomy.